Neurophysiological effects of needle trauma and intraneural injection in a porcine model: a pilot study. Issue 3 (27th November 2015) - Kirchmair, L.; Ströhle, M.; Löscher, W. N.; Kreutziger, J.; Voelckel, W. G.; Lirk, P.
Abstract : Background: Neurophysiological data are lacking in the research of nerve injury during regional anaesthesia. The aim of this pilot study was to establish a large animal model in order to test the hypothesis that needle trauma alone or in combination with intraneural injection would result in measurable nerve injury. Methods: The experimental set‐up was elaborated in four pre‐test animals. In the remaining animals ( n = 11), 22 sciatic nerves were randomly assigned to one of four groups: needle trauma ( n = 5) generated by ultrasound‐guided forced needle advancement; intraneural injection of 2.5 ml saline ( n = 6); intraneural injection of 5 ml saline ( n = 6); extraneural injection of 5 ml saline ( n = 5) as control group. Compound muscle action potential (CMAP) amplitudes as well as latencies were taken as outcome parameter and monitored over 180 min. Sonographic assessments were performed simultaneously. Results: Following needle trauma and intraneural injection, CMAP amplitudes declined significantly over 180 min ( P < 0.001). The control group showed no electrophysiological alterations. At 60 min, decreases in amplitude were significant after needle trauma ( P = 0.04) and intraneural injection of 2.5 ml ( P = 0.045), and highly significant after injection of 5 ml ( P = 0.006) when compared to controls. Sustained nerve swelling was observed after intraneural injection, but not after needle trauma and perineural injection. Conclusions: Isolated mechanical trauma caused by forced needle advancement alone or in combination with intraneural injection of saline was followed by a significant decline in CMAP amplitudes indicating conduction block due to disruption of myelin or axon loss (pseudo‐conduction block).